GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 21 Oct 2019, 08:19 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  If d = (c - b)/(a - b), then b =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 58415
If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags 00:00

Difficulty:   15% (low)

Question Stats: 84% (01:38) correct 16% (01:32) wrong based on 61 sessions

HideShow timer Statistics

If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

_________________
Math Expert V
Joined: 02 Sep 2009
Posts: 58415
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

CEO  D
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2978
Location: India
GMAT: INSIGHT
Schools: Darden '21
WE: Education (Education)
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

Bunuel wrote:
If d = (c - a)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

d = (c - a)/(a - b)

i.e. (a-b) = (c-a)/d

i.e. b = a - (c-a)/d

i.e. b = [ad - (c-a)]/d

Bunuel Are the options correct???
_________________
Prosper!!!
GMATinsight
Bhoopendra Singh and Dr.Sushma Jha
e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772
Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi
http://www.GMATinsight.com/testimonials.html

ACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION
Math Expert V
Joined: 02 Sep 2009
Posts: 58415
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

GMATinsight wrote:
Bunuel wrote:
If d = (c - a)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

d = (c - a)/(a - b)

i.e. (a-b) = (c-a)/d

i.e. b = a - (c-a)/d

i.e. b = [ad - (c-a)]/d

Bunuel Are the options correct???

There was a typo: it's d = (c - b)/(a - b) NOT d = (c - a)/(a - b). Edited. Thank you for noticing!
_________________
Senior PS Moderator V
Joined: 26 Feb 2016
Posts: 3335
Location: India
GPA: 3.12
If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

1
Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

We are given that d = $$\frac{c-b}{a-b}$$

Cross multiplying, da - db = c - b

$$db - b = c - ad$$ -> $$b(d - 1) = c - ad$$ -> $$b = \frac{(c - ad)}{(d - 1)}$$

Therefore, b = $$\frac{(c - ad)}{(d - 1)}$$ (Option D)

Alternate approach

If c=4,b=1,a=2 then d=4-1/2-1 = 3

Now substutiting in the available answer options,

A. (c - d)/(a - d) = (4-3)/(2-3) = -ive

B. (c + d)/(a + d) = (4+3)/(2+3) = 7/5

C. (ca - d)/(ca + d) = (8-3)/(8+3) = 5/11

D. (c - ad)/(1 - d) = (4-6)/(1-3) = -2/-2 = 1

E. (c + ad)/(d -1) = (4+6)/2 = 10/2 = 5 (Option D)
_________________
You've got what it takes, but it will take everything you've got
CEO  D
Status: GMATINSIGHT Tutor
Joined: 08 Jul 2010
Posts: 2978
Location: India
GMAT: INSIGHT
Schools: Darden '21
WE: Education (Education)
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

d = (c - b)/(a - b)

i.e. da - bd = c-b

i.e. bd - b = da - c

i.e. b (d-1) = da-c

i.e. b = (da - c) / (d-1) or

b = (c - ad)/(1 - d)

_________________
Prosper!!!
GMATinsight
Bhoopendra Singh and Dr.Sushma Jha
e-mail: info@GMATinsight.com I Call us : +91-9999687183 / 9891333772
Online One-on-One Skype based classes and Classroom Coaching in South and West Delhi
http://www.GMATinsight.com/testimonials.html

ACCESS FREE GMAT TESTS HERE:22 ONLINE FREE (FULL LENGTH) GMAT CAT (PRACTICE TESTS) LINK COLLECTION
Target Test Prep Representative D
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8117
Location: United States (CA)
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

First, we multiply both sides by (a - b) and expand the left side:

d(a - b) = c - b

da - db = c - b

Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side:

b - db = c - da

On the left side of the equation, factor out the common factor b from both terms:

b(1 - d) = c - da

Divide both sides by (1 - d), and now b is by itself on the left side of the equation:

b = (c - da)/(1 - d)

_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Intern  Joined: 07 Jul 2017
Posts: 1
If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

pushpitkc wrote:
Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

We are given that d = $$\frac{c-b}{a-b}$$

Cross multiplying, da - db = c - b

$$db - b = c - ad$$ -> $$b(d - 1) = c - ad$$ -> $$b = \frac{(c - ad)}{(d - 1)}$$

Therefore, b = $$\frac{(c - ad)}{(d - 1)}$$ (Option D)

Alternate approach

If c=4,b=1,a=2 then d=4-1/2-1 = 3

Now substutiting in the available answer options,

A. (c - d)/(a - d) = (4-3)/(2-3) = -ive

B. (c + d)/(a + d) = (4+3)/(2+3) = 7/5

C. (ca - d)/(ca + d) = (8-3)/(8+3) = 5/11

D. (c - ad)/(1 - d) = (4-6)/(1-3) = -2/-2 = 1

E. (c + ad)/(d -1) = (4+6)/2 = 10/2 = 5 (Option D)

I understand the algebraic approach, but I can not get alternative approach. Using your variables I arrived at the correct answer, but when I use the variables
a=1 , b=2, c=3, and d=-1, I get answer A and D equal to 2. Why can I not use this set of variables?
Intern  Joined: 04 Aug 2014
Posts: 2
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

ScottTargetTestPrep wrote:
Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

First, we multiply both sides by (a - b) and expand the left side:

d(a - b) = c - b

da - db = c - b

Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side:

b - db = c - da

On the left side of the equation, factor out the common factor b from both terms:

b(1 - d) = c - da

Divide both sides by (1 - d), and now b is by itself on the left side of the equation:

b = (c - da)/(1 - d)

I can follow your manipulations once I see the solution but how did you know - in two minutes - those were the right manipulations to get to the answer choices?..

I got stuck with b=c-da+db (which is correct but does not correspond to any answer choices...). Manager  B
Joined: 28 Jan 2018
Posts: 50
Location: Netherlands
Concentration: Finance
GMAT 1: 710 Q50 V36 GPA: 3
If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

$$d$$ = $$\frac{(c-b)}{(a-b)}$$ => $$d(a - b) = c - b$$ => $$ad - bd = c - b$$ =>
$$b - bd = c - ad$$ => $$b(1 - d) = c - ad$$ => $$b$$ = $$\frac{(c-ad)}{(1-d)}$$

Manager  B
Joined: 28 Jan 2018
Posts: 50
Location: Netherlands
Concentration: Finance
GMAT 1: 710 Q50 V36 GPA: 3
Re: If d = (c - b)/(a - b), then b =  [#permalink]

Show Tags

grgsky wrote:
ScottTargetTestPrep wrote:
Bunuel wrote:
If d = (c - b)/(a - b), then b =

A. (c - d)/(a - d)

B. (c + d)/(a + d)

C. (ca - d)/(ca + d)

D. (c - ad)/(1 - d)

E. (c + ad)/(d -1)

First, we multiply both sides by (a - b) and expand the left side:

d(a - b) = c - b

da - db = c - b

Now, since our goal is to solve for b, we put all terms containing b on the left side of the equation and all other terms on the right side:

b - db = c - da

On the left side of the equation, factor out the common factor b from both terms:

b(1 - d) = c - da

Divide both sides by (1 - d), and now b is by itself on the left side of the equation:

b = (c - da)/(1 - d)

I can follow your manipulations once I see the solution but how did you know - in two minutes - those were the right manipulations to get to the answer choices?..

I got stuck with b=c-da+db (which is correct but does not correspond to any answer choices...). hi, ideally in these kind of questions, you'll want to concentrate all the value that related to b on one side of the equation and the rest on the other side. Check my solution above for details Re: If d = (c - b)/(a - b), then b =   [#permalink] 20 Mar 2018, 10:27
Display posts from previous: Sort by

If d = (c - b)/(a - b), then b =

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  